Pengaruh Penggunaan Media Sosial terhadap Kinerja Pemasaran selama Pandemi Covid-19 dengan Mediasi Kemampuan Inovasi dan Kemampuan Branding (Studi pada Pelaku UMKM yang Menggunakan Media Sosial). - Anggraeni, Mia; Sanaji, Sanaji (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The Covid-19 virus that spreads globally has an impact on economic growth in Indonesia. Several business sectors have experienced a decline in performance due to the government's restrictions on outdoor activities to prevent the spread of this virus. For this reason, SMEs must be able to adjust their marketing channels from offline to online to optimize marketing performance during the Covid-19 pandemic. One of the online marketing tools is social media. This study investigates the use of social media on marketing performance with innovation capability and branding capability as mediating variables. This study uses 200 samples of respondents who are the owners of SMEs that collected through an online questionnaire. We use the Partial Least Square (PLS) method to test the hypothesis. The results of this study indicate that social media has a significant effect on innovation capability and branding capability and helps SMEs improve their marketing performance. This research also proves that innovation capability and branding capability successfully mediate the influence of the relationship between social media use on marketing performance.